Controlling and Fine-Tuning Charge-Transfer Emission in 2,6-Dicyanoaniline Multichromophores Prepared through Domino Reactions: Entry to a Potentially New Class of OLEDs - Plass, Fabian; Bönisch, Simon; Held, Felix; Ullrich, Tobias; Fischer, Florian; Guryev, Anton; Görling, Andreas; Kahnt, Axel; Tsogoeva, Svetlana (Journal of Organic Chemistry, 2021)
Substituted 2,6-dicyanoanilines are versatile electron donor-acceptor compounds, which have recently received considerable attention, since they exhibit strong fluorescence and may have utility in the synthesis of fluorescent materials, non-natural photosynthetic systems, and materials with nonlinear optical properties. The majority of known synthetic procedures are, however, "stop-and-go"reaction processes involving time-consuming and waste-producing isolation and purification of product intermediates. Here, we present the synthesis of substituted 2,6-dicyanoanilines via atom-economical and eco-friendly one-pot processes, involving metal-free domino reactions, and their subsequent photochemical and photophysical measurements and theoretical calculations. These studies exhibit the existence of an easily tunable radical ion pair-based charge-transfer (CT) emission in the synthesized 2,6-dicyanoaniline-based electron donor-acceptor systems. The charge-transfer processes were explored by photochemical and radiation chemical measurements, in particular, based on femtosecond laser photolysis transient absorption spectroscopy and time-resolved emission spectroscopy, accompanied by pulse radiolysis and complemented by quantum chemical investigations employing time-dependent density-functional theory. This chromophore class exhibits a broad-wavelength-range fine-tunable charge recombination emission with high photoluminescence quantum yields up to 0.98. Together with its rather simple and cost-effective synthesis (using easily available starting materials) and customizable properties, it renders this class of compounds feasible candidates as potential dyes for future optoelectronic devices like organic light-emitting diodes (OLEDs).
CRIS-Team Scopus Importer:2021-05-14

Enantioselective Cycloaddition Reactions Catalyzed by BINOL-Derived Phosphoric Acids and N-Triflyl Phosphoramides: Recent Advances - Held, Felix; Grau, Dominik; Tsogoeva, Svetlana (Molecules, 2015)
Over the last several years there has been a huge increase in the development and applications of new efficient organocatalysts for enantioselective pericyclic reactions, which represent one of the most powerful types of organic transformations. Among these processes are cycloaddition reactions (e.g., [3+2]; formal [3+3]; [4+2]; vinylogous [4+2] and 1,3-dipolar cycloadditions), which belong to the most utilized reactions in organic synthesis of complex nitrogen- and oxygen-containing heterocyclic molecules. This review presents the breakthrough realized in this field using chiral BINOL-derived phosphoric acids and N-triflyl phosphoramide organocatalysts.
Keywords: cycloaddition reactions; BINOL-derived phosphoric acids; N-triflyl phosphoramides; enantioselective pericyclic reactions

Facile access to potent antiviral quinazoline heterocycles with fluorescence properties via merging metal-free domino reactions - Held, Felix; Guryev, Anton; Fröhlich, Tony; Hampel, Frank; Kahnt, Axel; Hutterer, Corina; Steingruber, Mirjam; Bahsi, Hanife; Von Bojnicic-Kninski, Clemens; Mattes, Daniela S.; Foertsch, Tobias C.; Nesterov-Mueller, Alexander; et al. (Nature Communications, 2017)
Most of the known approved drugs comprise functionalized heterocyclic compounds as subunits. Among them, non-fluorescent quinazolines with four different substitution patterns are found in a variety of clinically used pharmaceuticals, while 4,5,7,8-substituted quinazolines and those displaying their own specific fluorescence, favourable for cellular uptake visualization, have not been described so far. Here we report the development of a one-pot synthetic strategy to access these 4,5,7,8-substituted quinazolines, which are fluorescent and feature strong antiviral properties (EC50down to 0.6±0.1 μM) against human cytomegalovirus (HCMV). Merging multistep domino processes in one-pot under fully metal-free conditions leads to sustainable, maximum efficient and high-yielding organic synthesis. Furthermore, generation of artesunic acid-quinazoline hybrids and their application against HCMV (EC50down to 0.1±0.0 μM) is demonstrated. Fluorescence of new antiviral hybrids and quinazolines has potential applications in molecular imaging in drug development and mechanistic studies, avoiding requirement of linkage to external fluorescent markers.
EVALuna2:33762

Spatial modes of laser-induced mass transfer in micro-gaps - Foertsch, Tobias C.; Davis, Alex T.; Popov, Roman; Von Bojnicic-Kninski, Clemens; Held, Felix; Tsogoeva, Svetlana; Loeffler, Felix E.; Nesterov-Mueller, Alexander (Applied Sciences, 2019)
We have observed the concentric deposition patterns of small molecules transferred by means of laser-induced forward transfer (LIFT). The patterns comprised different parts whose presence changed with the experimental constraints in a mode-like fashion. In experiments, we studied this previously unknown phenomenon and derived model assumptions for its emergence. We identified aerosol micro-flow and geometric confinement as the mechanism behind the mass transfer and the cause of the concentric patterns. We validated our model using a simulation.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Aerosol; Bio-printing; Confinement; Deposition patterns; LIFT